Peran Literasi di Era Digital Dalam Menghadapi Hoaks dan Disinformasi di Media Sosial - Nisa, Khoirun (Impressive: Journal of Education, 2024)
This research aims to provide a solution to the importance of literacy in the digital era, to explain the importance of literacy in the digital era in dealing with hoaxes or false information on social media as well as strategies for increasing literacy in the digital era. Hoaxes can have a very detrimental impact, both on individuals and society as a whole. Therefore, it is important for people to always check the veracity of information before sharing it or taking action based on that information. With digital literacy, people can understand and manage information spread on social media. The research method used is a qualitative method with a library research approach. The literature study method involves collecting data by understanding and studying theories from various literature that are relevant to the research subject. Literacy in this digital era is the key to overcoming various challenges. Digital literacy is important in dealing with hoaxes, including the ability to identify hoaxes, evaluate the authenticity of information sources, understand the context of information, use tools, question information, and maintain online privacy and security. Digital literacy helps individuals become more intelligent, critical and responsible in consuming and disseminating information in the digital world.